Akuntansi dan Aplikasi Pesantren: Menuju Modernisasi Tata Kelola Pesantren - Sutrisno, Catur Ragil; Al Farisi, Salman; Ilmiani, Amalia; Khoiri, Habib; Agung Prasetya, Nanda (AKTSAR: Jurnal Akuntansi Syariah, 2024)
This study uses a quantitative descriptive method to describe the phenomenon accurately without testing a specific hypothesis. This study focuses on the financial governance of Islamic boarding schools in Pekalongan Regency by involving 44 ustadz/ustadzah as respondents who were selected randomly. Primary data were collected through questionnaires. The results of the study indicate that most Islamic boarding schools still maintain traditional learning methods (salaf), and some have combined formal curriculum. Regarding financial management, most Islamic boarding schools have a simple bookkeeping system, and some have adopted a more structured accounting system supported by accounting applications or integrated information systems. These findings underline the importance of accounting training and information system development to improve Islamic boarding school accountability. There is an urgent need for Islamic boarding schools to adapt to the demands of modern governance without sacrificing their traditions.